PENENTUAN KADAR AIR UBI KAYU MENGGUNAKAN PLAT KAPASITOR SEJAJAR - Rizki Amelia; Maksi Ginting; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
A research has been conducted on Determining Moisture Content of Cassava by Using Parallel Plate Capacitor . This experiment was carried out by perforning two methods: gravimetric and parallel plate capacitor. Methods gravimetric method was carried out to determine the water content as a standard while parallel plate capacitor while the method was performed to measure current so that water content of the sample can be determined. The samples were consisted of two types; white cassava and red cassava, 10 cm long, 5 cm wide and 0,5 cm thick. The measurement results showed that the water content of cassava whites ranged from 48,8% to 56% and cassava red ranged from 55,1% to 57,5%. The greater the water content, the greater the current.